2018
DOI: 10.5935/1981-2965.20180022
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento e composição centesimal do tambaqui (Colossoma macropomum) por diferentes cortes e categorias de peso

Abstract: Rendimento e composição centesimal do tambaqui (Colossoma macropomum) por diferentes cortes e categorias de peso Yield and centesimal composition of tambaqui (Colossoma macropomum) by different processing forms and weight categories

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
3
9
0
4
Order By: Relevance
“…Therefore, in fish such as tambaqui fry, moisture makes up about 65% of the fillet (Terrazas et al, 2002;Mendonça et al, 2011), while in the juvenile phase (Lima et al, 2018;Oliveira et al, 2020) up to adult (Sales & Maia, 2013;Mesquita, 2013;Lima et al, 2018) values can vary from 70 to 80% of water present in the meat, corroborating with the results presented here since both wild tambaqui (≈ 79.8) and farmed tambaqui (≈ 76.5) had similar average moisture levels. Other species of fish such as pacu (Piaractus mesopotamicus Holmberg, 1887) (Ramos et al, 2008;Cortez et al, 2010;Zuanazzi et al, 2013), tilápia (Oreochromis niloticus Linnaeus, 1758) (Cortez et al, 2010;Sales & Maia, 2012;Colpini et al, 2017) and piauçu (Leporinus microcephalus Garavello & Britski, 1988) (Lanzarin et al, 2017) showed the same pattern with moisture ranging from 60 to 80%, both for wild fish and for farmed fish.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, in fish such as tambaqui fry, moisture makes up about 65% of the fillet (Terrazas et al, 2002;Mendonça et al, 2011), while in the juvenile phase (Lima et al, 2018;Oliveira et al, 2020) up to adult (Sales & Maia, 2013;Mesquita, 2013;Lima et al, 2018) values can vary from 70 to 80% of water present in the meat, corroborating with the results presented here since both wild tambaqui (≈ 79.8) and farmed tambaqui (≈ 76.5) had similar average moisture levels. Other species of fish such as pacu (Piaractus mesopotamicus Holmberg, 1887) (Ramos et al, 2008;Cortez et al, 2010;Zuanazzi et al, 2013), tilápia (Oreochromis niloticus Linnaeus, 1758) (Cortez et al, 2010;Sales & Maia, 2012;Colpini et al, 2017) and piauçu (Leporinus microcephalus Garavello & Britski, 1988) (Lanzarin et al, 2017) showed the same pattern with moisture ranging from 60 to 80%, both for wild fish and for farmed fish.…”
Section: Discussionsupporting
confidence: 87%
“…Provavelmente a menor perda de peso por gotejamento e perda de peso por descongelamento, quando se aumentou o peso de abate dos animais, seja devido ao menor teor de umidade e maior de gordura que a carne dos peixes apresentaram com o avançar da idade. Essas pressuposições corroboram com Lima et al (2018), que observaram maior teor de lipídeos na carne dos peixes abatidos mais pesados, ao avaliarem a composição centesimal da carne de tambaqui com diferentes categorias de peso; com Botelho et al (2017), que verificaram redução da umidade da carne de tambaquis abatidos mais pesados, quando comparado com outras espécies abatidas mais leves; e com Kayan et al (2015), que também verificaram diminuição da umidade e aumento da gordura da carne dos peixes abatidos mais pesados.…”
Section: Variávelunclassified
“…O tambaqui (Colossoma macropomum Cuvier, 1818, Characidae, Serrasalminae), espécie nativa da bacia do Amazonas, desponta como a principal espécie de peixe cultivada na região Norte do Brasil. Esse fato se deve devido as inúmeras características que a espécie apresenta, como fácil manejo, rápido crescimento, alta rusticidade, bom rendimento de filé, carne de qualidade, e, também, porque ela se adapta às diversas condições de criação, além de apresentar valor econômico e ser muito apreciada pelo consumidor (ARAÚJO-LIMA e GOMES, 2010;GOMES et al, 2010;CARTONILHO e JESUS, 2011;FRANCO et al, 2013;LIMA et al, 2018;SANTOS et al, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In the present study, only the waste of tambaqui processing (viscera, fins, few scales, and gills) was used. Large tambaqui have high meat yield, but accumulate high volumes on non-edible fat in the viscera (Kubitza, 2004).The waste ensiled in the present study derived from tambaqui weighing 500 to 800g, which present low fat accumulation in the abdominal cavity, in addition of lower viscera yield and higher fillet yield compared with larger fish (Lima et al, 2018), consequently providing higher levels of protein, soluble carbohydrates (non-nitrogenous extract), insoluble carbohydrates (fibers) and gross energy.…”
Section: Digestibility and Physicochemical Characteristics Of Tambaqumentioning
confidence: 80%